2011
DOI: 10.1002/ibd.21337
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal tissue kallikrein-kinin system in inflammatory bowel disease

Abstract: Tissue kallikrein cleaves kininogens to release kinins. Kinins mediate inflammation by activating constitutive bradykinin receptor-2 (BR2), which are rapidly desensitized, and induced by inflammatory cytokines bradykinin receptor-1 (BR1), resistant to desensitization. Intestinal tissue kallikrein (ITK) may hydrolyze growth factors and peptides, whereas kinins are responsible for capillary permeability, pain, synthesis of cytokines, and adhesion molecule-neutrophil cascade. Our and others results have demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 86 publications
0
15
0
3
Order By: Relevance
“…Bradykinin and related kinins are produced from both blood (plasma kallikrein-kinin system) and tissues (tissue kallikreinkinin system) in response to inflammatory stimuli [87,88]. Bradykinin is a nine amino acid peptide (Arg-Pro-Pro-Gly-PheSer-Pro-Phe-Arg), formed from the kininogen precursor after proteolytic cleavage by tissue and plasma kallikrein.…”
Section: Roles Of Kinins In Airway Inflammation and Ahrmentioning
confidence: 99%
“…Bradykinin and related kinins are produced from both blood (plasma kallikrein-kinin system) and tissues (tissue kallikreinkinin system) in response to inflammatory stimuli [87,88]. Bradykinin is a nine amino acid peptide (Arg-Pro-Pro-Gly-PheSer-Pro-Phe-Arg), formed from the kininogen precursor after proteolytic cleavage by tissue and plasma kallikrein.…”
Section: Roles Of Kinins In Airway Inflammation and Ahrmentioning
confidence: 99%
“…The highest inhibitory effect can be observed in the activity of the extracellular serine peptidase (IC 50 about 8.8-4.06 × 10 −8 M, Table 2b). Similar ShPI-I inhibition could be observed for another serine peptidase that acts in the extracellular environment, tissue kallikrein (Delfin et al, 1996), that cleaves kininogens to release kinins secreted by exocrine glands (Stadnicki, 2011). It is known that T. cruzi epimastigote secretes two serine peptidases into the extracellular milieu (Santana et al, 1997;Silva-López et al, 2008).…”
Section: Effect Of Inhibitor On T Cruzi Serine Peptidasesmentioning
confidence: 85%
“…Intestinal kallikrein may degrade growth factors and peptides, whereas kinins are responsible for capillary permeability, pain, synthesis of cytokines, and the adhesion molecule neutrophil cascade. Recent studies have shown that kallikrein is present in intestinal goblet cells and is released into interstitial space during inflammation (74).…”
Section: Resultsmentioning
confidence: 99%